(untitled) (Editora Impacto Científico, 2025)
With the evolution of technology and its insertion in education, the current generations emerged, which carry predominant characteristics, and such need to be considered and considered as influences for the cognition of knowledge and for the subjects’ own development. In this context, the study considers the following problem: What are the main difficulties with the Screenagers Generation in the face of this new educational universe? Therefore, the general objective of the study is to relate the causes that make it difficult to adapt education, as well as interface designs, in the face of the new Screenagers Generation, which has, among its specific objectives, conceptualizing the course of generations and the arrival of the Screenagers Generation, correlating the possibilities for education and the creation of interface designs in this new universe, and present the challenges and impacts that represent the difficulties with the Screenagers Generation at the educational level. Therefore, initial contributions on the themes are appreciated, benefiting teachers and students, school institutions and government bodies, such as society, making education more inclusive, expressive and considerable. This is a methodological study based on research of a basic nature, with immediate and expandable results, having objectives with descriptive and explanatory directions, through a qualitative approach, whose study method incurs through bibliographical research. It is concluded that the Screenagers Generation brings challenges and possibilities that are speculative, however, that demonstrate profound changes at all levels, and for education such changes reflect difficulties due to the agglomeration of educational deficiencies.